Accounting of carbon sequestration and tradeoff under various climatic scenarios in alternative agricultural system: a comprehensive framework toward carbon neutrality - Ansari, Meraj Alam; Ravisankar, Natesan; Shamim, Mohammad; Rani, Meenu; Prusty, Ashisa K.; Singh, Raghuveer; K. J, Raghavendra; Joshi, Himanshu; Kumar, Sunil; Panwar, Azad Singh; Kumar, Mahesh (Frontiers in Sustainable Food Systems, 2024)
The increase in atmospheric CO2 concentration, which mainly is attributed to fossil-fuel combustion and deforestation, is often suggested as one of the prime causative factors towards accelerated global warming. This commends for sequestration of atmospheric carbon under terrestrial systems to partially offset fossil-fuel emissions. Concerning the same, agricultural sector presents an extensive opportunity, especially for countries like India where over 55% of the population is engaged in the agriculture sector. Sequestering atmospheric carbon in agriculture requires the adoption of climate-resilient alternative agriculture practices without compromising food security. The deliberated study highlights the options of alteration in current conventional farming practices and its economic evaluation for sequestrating carbon under two Climate Change (CC) scenarios, viz., RCP 4.5 and 8.5, over three temporal scales, i.e., 2020, 2030, and 2050. Considering the current land-use pattern and existing growth rate in landuse shifting, three land-use policies, namely, Business as Usual (BaU), Optimistic, and Pessimistic scenario, integrated with CC scenarios were contemplated. Six possible futuristic scenarios were generated for the assessment of carbon sequestration and its valuation following the Integrated valuation of ecosystem services and tradeoff (InVEST) model. The results suggested that across the studied region adopting an optimistic policy over BaU and pessimistic scenario, carbon can sequestrate an additional 0.64 to 1.46 Mt (2.35 to 5.36 million tonne CO2e) having an economic value 193.4 to 504.8 million USD. Moreover, the outcomes of the study advocated for the policy for carbon credit in the agriculture sector, which shall contribute towards meeting various Nationally determined contributions (NDCs) and sustainable development goals (SDGs) as well.